Study of sugarcane metabolism modulation by the plant pathogenic fungus Sporisorium scitamineum - Schaker, Patricia Dayane Carvalho (2017)
This thesis presents a more in-depth understanding of the interaction between the pathogenic fungus Sporisorium scitamineum and sugarcane, a disease known as \"cane smut\". The development of a long structure like a \"whip\" from the meristem of infected plants is the main characteristic of the disease, allowing the effective dispersion of teliospores in the field. Infected plants have a reduced sucrose content and juice quality, leading to considerable economic losses. In the first chapter, the gene expression profile of the pathogen during its development in planta - in the first moments of infection and after the emission of the whip - and in vitro was evaluated using the RNAseq technique. Were analyzed genes preferentially expressed in each condition, differentially expressed in comparison to its growth in vitro, and expressed only during interaction. The results allowed the identification of some potential pathogenicity mechanisms, active effectors and gene clusters expressed only during interaction. In the second chapter, the transient expression technique was used to determine the target cell compartment of some of the candidate effectors and to establish a viable protocol for the study of S. scitamineum proteins. The four putatively secreted genes most expressed during the initial moments of the interaction were fused to the gene encoding the fluorescent green protein (Citrine) and expressed in Nicotiana benthamiana. The results of confocal microscopy and westernblots indicated an accumulation of each candidate protein in the membrane, cytosol and/or nucleus, in addition to the occurrence of post-translational modifications. These data offer new study opportunities for the identification of plant proteins that interact with such effectors. In the third chapter, the transcriptional responses of sugarcane in the first moments of a compatible interaction and after the development of the whip were analyzed using again the data obtained from the dual RNAseq cane-smut. Among the main responses, was identified an increase in MADS-type transcription factors expression, indicating that the whip development may use a route similar to flowering, whose signaling seems to start as early as the colonization. In addition, whip development is accompanied by increased transcription of genes involved in energetic pathways, and hormones synthesis and signaling pathways. Genes encoding RGAs were differentially expressed and may be related to pathogen effector\'s recognition. In the fourth chapter, the metabolic profile of sugarcane was evaluated during disease progression, confirming that in the meristem of infected plants carbon allocation is channeled to energetic pathways, besides the regulation of several amino acids and changes in plant cell composition in response to whip development. Metabolomics approach also allowed the identification of a probable mycotoxin derived from S. scitamineum. The results obtained in this study contributed to increase the understanding of the interaction between S. scitamineum and sugarcane that is characterized by high complexity and specialization to the host, and can be used in a way to help the characterization of resistant varieties and contribute to the improvement of sugarcane with resistance to smut.